Pengembangan Perangkat Pembelajaran Matematika Berbasis Konstruktivisme Di Smp Negeri 1 Kemusu - Manan, Uffun Ainullia, Prof. Dr. Sutama, M.Pd, Dr. Sabar Narimo, M.M., M.Pd (2017)
UFFUN AINULLIA MANAN. Q.100130004. DEVELOPMENT OF CONSTRUCTIVISM BASED LEARNING MATHEMATICS IN SMP NEGERI 1 KEMUSU. Thesis. Master Program of Educational Administration. Graduate School Muhammadiyah Surakarta University. The purpose of this research are: (1) Describe the RPP Mathematics learning device is used so far,(2) Describe the development of the RPP Mathematics learning device based on Constructivism,(3) Test the effectiveness of the development of RPP Mathematics learning device based on constructivism. This research is a research development (Research and Development). Triangulation techniques are used to collect data with participative observation methods, in-depth interviews, documentation and tests. Data analysis techniques consist of two components namely data reduction and data presentation. Results and discussion of the research are (1) Learning tool of RPP Mathematicsthat have been applied still use RPP Mathematics school in general, in the core activities the students have not maximally built their own knowledge for the discovery of new concepts. (2) Development of the RPP Mathematics learning device based on Constructivism with learning design includes 5 stages: Orientation, Eliciation, Ideal Restructuring, Use of Ideas, and Reviews that are implemented on core activities, (3) The value of concept comprehension test using RPP based on Constructivism, the average grade is 79.02 from 70.00. Students who scored ≥ 75 are 18 students or 78.26%. (Math KKM = 75). So the classical learning of mathematics is complete. Key Word : constructivism, concepts understanding